Trigonometria no triângulo retângulo: construindo uma aprendizagem significativa - Silva, Sílvio Alves da (2005)
The aim of this work is to was investigating an approach to the teaching of trigonometry in the right triangle, where it was pretended to present the concepts underlying the trigonometric ratios sine, cosine and tangent. Our research hypotesis is that we can make a signyficative learning to the student through problem-situations that articuleded the geometry construction and the figural tratament in the abording of the trigonometric relations. We prepared a didactic sequence with four activities and we applied, supporting by Engineering Didactic fundaments, to aswer if the production of the teaching sequence abording the geometry constructions and geometry transformations articuladed to the figural tratament gives a significative learning to the students of the inicial serie of the high school of the concepts in the trigonometry right triangle. For to answer the research question, we analised the conceptions of the students over the aplication of the sequence, the resolution of the situations in the activities and the discution of this situations. We concluded that there was conceptual development of the students in the trigonometry relations